Pengukuran Kualitas Air Limbah Sawit Berdasarkan Baku Mutu Air Limbah Menggunakan AAS - Rusdianto Rusdianto; Syachrul Ivandi; Tri Kusmita; Ilhafurroihan Apriliazmi (Jurnal Riset Fisika Indonesia, 2023)
Palm oil industry waste is waste generated from the palm oil processing process. Palm oil liquid waste generally contains heavy metals, one of which is Cu and Zn. The presence of excessive Cu and Zn heavy metals can have a negative impact on living things and the surrounding environment. In this journal, the determination of the heavy metal content of Cu and Zn in palm oil wastewater was carried out using the AAS method with acetylene gas at a wavelength of 324.8 nm to determine the content of Cu metal content and at a wavelength of 213.9 nm to determine the Zn metal content. The results of determining the content of heavy metals Cu and Zn in sempel 1, 2 and 3 contained in palm oil wastewater which are still below the maximum limit of the quality standards obtained, namely less than 2 ppm for Cu metal and less than 5 ppm for Zn metal. utilized by living things and the surrounding environment.